A modified ctab-based protocol for total RNA extraction from the medicinal plant Impatiens balsamina (Balsaminaceae) for next-generation sequencing studies - Foong, Lian Chee; Siong Hock Ho, Anthony Hock Ho; Lim, Yang Mooi; Tam, Sheh May (Penerbit Universiti Kebangsaan Malaysia, 2017)
High RNA quality, integrity and reproducibility are essential for functional genomics study involving library preparation and sequencing using next generation sequencing (NGS) technologies. The medicinal herbaceous plant, Impatiens balsamina, possess a rich source of diverse bioactive compounds including polysaccharides and phenolic compounds, hindering the extraction of high quality total RNAs. Four existing RNA extraction protocols were performed using fresh leaf material of I. balsamina, namely the CTAB method, the TRI reagent® method, modified TRI reagent® method and a commercial kit but the results were unsatisfactory. This led to the development of a modified CTAB protocol by combining CTAB/ polyvinylpyrrolidone (PVP) extraction with using commercial spin column purification for successful isolation of high quality total RNA from the leaf material of I. balsamina, that is suitable for NGS applications (RIN values > 7). This new method also successfully extracted total RNA from flower buds and capsules of I. balsamina.